Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Our platform connects you with professionals ready to provide precise answers to all your questions in various areas of expertise. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

TIME REMAINING
58:53
The solution to the system of equation below is (−2, −1).

2x − 3y = −1
11x − 9y = −13

When the first equation is multiplied by −3, the sum of the two equations is equivalent to 5x = −10.


Sagot :

Answer:

XD is an emoticon commonly used to symbolize dying from laughter. It represents 2 closed eyes with the X and mouth with the D.

The solution of the equations is (-2, -1)

System of equation:

2x - 3y = -1

11x  - 9y = -13

Using elimination method let multiply the first equation by -3.

Therefore,

-6x + 9y = 3

11x - 9y = -13

5x = -10

x = -10 / 5

x = -2

let's find y as follows;

2(-2) - 3y = -1

-4 - 3y = -1

-3y = -1 + 4

-3y = 3

y = 3 / -3

y = -1

learn more on system of equation here: https://brainly.com/question/1451150

Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.